1979
DOI: 10.1111/j.1532-5415.1979.tb06128.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity Study of the Short Portable Mental Status Questionnaire for the Elderly*

Abstract: The short, portable mental status questionnaire (SPMSQ) developed by Pfeiffer has several advantages over previous short instruments designed to assess the intellectual functioning of older adults. It is based upon data from both institutionalized and community‐dwelling elderly. Although Pfeiffer outlined a four‐group classification, he used two groups in his initial validation study: (a) intact/mildly impaired, and (b) moderately/severely impaired. The present study compared clinicians' ratings with those bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…Previously test‐retest correlations of SPMSQ at four‐week intervals have been 0.82 2 . Previous validity studies of the SPMSQ have shown a positive predictive value of 82.7% to 92.3% to detect moderate OBS 2,13,14 …”
Section: Discussionmentioning
confidence: 97%
“…Previously test‐retest correlations of SPMSQ at four‐week intervals have been 0.82 2 . Previous validity studies of the SPMSQ have shown a positive predictive value of 82.7% to 92.3% to detect moderate OBS 2,13,14 …”
Section: Discussionmentioning
confidence: 97%
“…After completing the consent process, subjects completed Patient Health Questionnaire (PHQ9) [11] screening either in person or on the phone with the trained research assistant. Women unable to complete the informed consent process, participate in data collection, scoring <20 on the Short Portable Mental Status Questionnaire [12], or women deemed actively suicidal by our screening protocol were excluded. All women enrolled in the parent study completed baseline visit study forms at the time of enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…13 More than half of all institutionalized long-stay patients suffer from severe dementia.3,4 Dementia is a burden also in general hospitals. In medical wards the occurrence of all organic brain syndromes varies from 2.6% to 37%,MO and that of dementia from 1.3% to 15%.…”
mentioning
confidence: 99%